Cell Alignment on Graphene–Amyloid Composites. Issue 18 (25th June 2018) - Das, Subhadeep; Kumawat, Mukesh K.; Ranganathan, Srivastav; Kumar, Rakesh; Adamcik, Jozef; Kadu, Pradeep; Padinhateeri, Ranjith; Srivastava, Rohit; Mezzenga, Raffaele; Maji, Samir K.
Abstract: Graphene‐based hybrid nanomaterials have been shown to have great potential in various biotechnology applications including enzyme sensing and bone tissue engineering. Harnessing the unique properties of graphene and material strength of amyloids, a graphene–amyloid composite film is developed that can self‐organize into periodic troughs and crests without the need of lithographic techniques or etching. The topographies generated by the film provide powerful modulators of contact and guidance to neural precursor cells, enabling efficient cellular polarization and differentiation. Using molecular dynamic simulations and high‐resolution atomic force microscopy, the amyloidogenicity and handedness of matured amyloid nanofibrils to the micropatterns generated on the dried film are also correlated. These insights provide principles for peptide designing for generation of micropatterned, cell adhesive conductive substrates for optimal cell alignment and differentiation. Abstract : Synthesis of amyloid–graphene nanocomposites for developing unique micropatterned substrate. The patterns are self‐generated on drying the film on a glass substrate and do not require sophisticated lithographic techniques or etching. This conductive substrate with periodic troughs and crests aligns mammalian neuronal cells along its troughs as well as helps them differentiate.